(untitled) (Research, Society and Development, 2020)
Plastics in their various forms are increasingly present in human life, including packaging and household utensils. Such use may be associated with damage to the environment, as well as human health, since plastic materials in contact can migrate to water and food. For this reason, this study aimed to understand the perception of the population of the city of Uruçuí-PI in relation to the use of plastic packaging and its adverse effects on human and environmental health. The survey was conducted with 197 residents of the city of Uruçuí. In the invitation made by WhatsApp, the participants were informed of the research objectives and agreed to a Free and Informed Consent Form (ICF). For data collection, a semi-structured questionnaire was criated in Google Forms platform. The results obtained show that the Environmental Education (EE) theme is worked superficially in the school environment of Uruçuí-PI, and that issues related to plastic packaging are also not being discussed effectively in schools and social media. It was observed that some participants are aware of the migrating properties of plastics, but are unaware of the specific compounds and continue to use plastic materials in conditions that can be harmful to health. It is concluded, therefore, that the use of plastic packaging for food storage needs to be better addressed and that educational institutions should encourage EE actions at all levels and work in an interdisciplinary way, in view of its relevance to public health and environmental.